Neutrophil‐derived MRP‐14 is up‐regulated in infectious osteomyelitis and stimulates osteoclast generation. Issue 4 (12th March 2015) - Dapunt, Ulrike; Giese, Thomas; Maurer, Susanne; Stegmaier, Sabine; Prior, Birgit; Hänsch, G. Maria; Gaida, Matthias M.
Abstract : MRP‐14 is highly expressed in tissue and peripheral blood of patients with implant‐associated infections, and provides a link between bacterial bone infections and bone degradation. Abstract : Bone infections of patients with joint replacement by endoprosthesis (so called "periprosthetic joint infection") pose a severe problem in the field of orthopedic surgery. The diagnosis is often difficult, and treatment is, in most cases, complicated and prolonged. Patients often require an implant exchange surgery, as the persistent infection and the accompanying inflammation lead to tissue damage with bone degradation and consequently, to a loosening of the implant. To gain insight into the local inflammatory process, expression of the proinflammatory cytokine MRP‐14, a major content of neutrophils, and its link to subsequent bone degradation was evaluated. We found MRP‐14 prominently expressed in the affected tissue of patients with implant‐associated infection, in close association with the chemokine CXCL8 and a dense infiltrate of neutrophils and macrophages. In addition, the number of MRP‐14‐positive cells correlated with the presence of bone‐resorbing osteoclasts. MRP‐14 plasma concentrations were significantly higher in patients with implant‐associated infection compared with patients with sterile inflammation or healthy individuals, advocating MRP‐14 as a novel diagnostic marker. A further biologic activity of MRP‐14 was detected: rMRP‐14 directly induced the differentiation of monocytes to osteoclasts, thus linking the inflammatory response in implant infections with osteoclast generation, bone degradation, and implant loosening.